Evaluation of in-vessel co-composting of yard waste and development of kinetic models for co-composting - K. M. Sangamithirai; J. Jayapriya; J. Hema; Ravi Manoj (International Journal of Recycling of Organic Waste in Agriculture)
Background Organic solid waste management is a major challenge in high population density areas like apartments, educational institutions, hospitals, etc., as their disposal with other wastes could not only lead to issues like vector menace, odour generation but also would lead to loss of resources that could be reused such as nutrients which will benefit soil. In places like educational institutions, the major portion of waste generated is organic waste, especially food waste and yard waste from the campus, apart from paper waste. Composting is an organic waste treatment method that is cost effective and leads to resource recovery. In this study, the characteristics of composting of yard waste and co-composting of yard waste with wastes generated in an institution (university campuses of Anna University, Chennai, India) are examined. The composts were characterized in terms of total solids, volatile solids, pH, electrical conductivity, carbon: nitrogen (C:N) ratio and total Kjeldahl nitrogen. The stability index and germination index of the compost were assessed. Results The C:N ratio of all the different composts (except the one generated from yard with canteen waste consisting of vegetable waste) produced in this study has a value less than 30:1, which satisfies the basic requirements for the compost. It was also observed that the mature compost from these feedstocks did not have heavy metals at toxic levels. Conclusion This study demonstrated that the co-composting of yard wastes with paper and canteen wastes (fruit, coffee grounds, tea leaf waste) could produce value-added products. In addition to that, kinetic models were developed to predict the decomposition rate constant of the process.